An optogenetic method for the controlled release of single molecules - Kashyap, Purba; Bertelli, Sara; Cao, Fakun; Kostritskaia, Yulia; Blank, Fenja; Srikanth, Niranjan A.; Schlack-Leigers, Claire; Saleppico, Roberto; Bierhuizen, Dolf; Lu, Xiaocen; Nickel, Walter; Campbell, Robert E.; et al. (Nature methods, 2024)
We developed a system for optogenetic release of single molecules in cells. We confined soluble and transmembrane proteins to the Golgi apparatus via a photocleavable protein and released them by short pulses of light. Our method allows for a light dose-dependent delivery of functional proteins to the cytosol and plasma membrane in amounts compatible with single-molecule imaging, greatly simplifying access to single-molecule microscopy of any protein in live cells. We were able to reconstitute ion conductance by delivering BK and LRRC8/volume-regulated anion channels to the plasma membrane. Finally we were able to induce NF-kB signaling in T lymphoblasts stimulated by interleukin-1 by controlled release of a signaling protein that had been knocked out. We observed light-induced formation of functional inflammatory signaling complexes that triggered phosphorylation of the inhibitor of nuclear factor kappa-B kinase only in activated cells. We thus developed an optogenetic method for the reconstitution and investigation of cellular function at the single-molecule level.
Gesehen am 31.07.2024